RECOVERY ASET DAERAH YANG DIJADIKAN AGUNAN OLEH PIHAK KETIGA DALAM PERJANJIAN KERJASAMA DENGAN BUMD - Khairus Febryan Fitrahady; Ahmad Zuhairi; M. Riadhussyah (Arena Hukum, 2020)
ABSTRACTThis paper examines the inability of local governments to recover land assets that have been included as capital for regional-owned enterprises (BUMD). The problem arises when the land is used as an object for collateral by a third party because BUMD is unable to fulfill the achievements in the agreement. This normative research uses a statutory, conceptual and case approach. As a result, the West Lombok Regional Government is still unable to recover regional assets that have been used as collateral by third parties on the basis of a cooperation agreement with BUMD. The land is the capital that is included by the Regional Government to BUMD. Land which becomes the object of capital participation does not automatically transfer to BUMD if the transfer mechanism is not passed and is considered permanent as a regional asset. However, if the Regional Government has approved the land pledge process to the Bank through the general meetings of shareholders (GMS) mechanism, the Government will be very powerless to carry out recovery. However, the regional government could be the losing party if at any time the BUMD cannot fulfill its achievements and the land is auctioned off by the Bank.Â ABSTRAKTulisan ini mengkajiÂ  ketidakmampuan Pemerintah Daerah melakukan recovery aset tanah yang telah disertakan sebagai modal kepada BUMD. Permasalahan muncul ketika tanah tersebut dijadikan obyek agunan oleh pihak ketiga karena BUMD tidak mampu memenuhi prestasi dalam perjanjian. Penelitian normatif ini menggunakan pendekatan perundang-undangan, konseptual dan pendekatan kasus. Hasilnya, Pemerintah Daerah Lombok barat hingga saat ini masih tidak mampu untuk melakukan recovery terhadap aset daerah yang sudah dijadikan agunan oleh Pihak ketiga dengan dasar perjanjian kerjasama dengan BUMD. Tanah tersebut merupakan modal yang disertakan oleh Pemerintah Daerah kepada BUMD. Tanah yang menjadi obyek penyertaan modal tersebut tidak otomatis beralih kepada BUMD jika mekanisme pengalihan tidak dilalui dan dianggap tetap sebagai aset daerah. Namun jika Pemerintah Daerah telah menyetujui proses pengagunan tanah tersebut kepada Bank melalui mekanisme RUPS, Pemerintah akan sangat tidak berdaya untuk melakukan recovery. Namun, pemerintah daerah dapat menjadi pihak yang dirugikan jika sewaktu-waktu BUMD tersebut tidak dapat memenuhi prestasi dan tanah tersebut dilelang oleh Bank.